A comparative study of oral iron and intravenous iron in iron deficient antenatal mothers - G., Suganya; Vimala, D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim of the study is to compare the efficacy, tolerance and compliance between oral iron and intravenous infusion of iron in iron deficient antenatal mother. Methods: This is a prospective randomised clinical and interventional study in the department of Obstetrics and Gynaecology in Vinayaka Mission Kirupananda Variyar Medical College and Hospital. The antenatal women attending the antenatal op were screened for Hb status. Those antenatal women of gestational age 16-34 weeks with Hb level between 7-10g% and diagnosed to have iron deficiency anemia by peripheral smear and serum ferritin were included in this study after getting informed consent. The total numbers of 100 mothers were allotted into two major groups, group A and group B of 50 subjects each. Group A: 50 pregnant women given oral iron supplementation (carbonyl iron 100 mg twice a day). Group B: 50 pregnant women given intravenous iron sucrose therapy after calculating the total iron requirement. The rise in hemoglobin in both the groups were compared Results: In this study the mean rise of hemoglobin in carbonyl iron was 0.914±0.20 gm% whereas in iron sucrose group was 2.43±0.20gm%. This showed that iron sucrose (i.v) had better rise in Hb than carbonyl iron (oral). Conclusions: The present study revealed that intravenous iron sucrose therapy was better tolerated with higher increase in mean haemoglobin compared to oral iron therapy. There were no serious side effects with intravenous iron sucrose therapy. Intravenous iron sucrose is a good substitute to oral iron therapy in moderate anaemia.